Impact of Brucellosis on Reproductive Performance of Small Ruminants in Al-Qaryat, Libya - Akhlaas Dakheel; Najat Almabrouk (AlQalam Journal of Medical and Applied Sciences, 2026)
Brucellosis is among the zoonotic diseases that have been affecting small ruminants and have had an impact on them, especially during their reproductive period. Therefore, the aim of this study was mainly to establish the prevalence of brucellosis in the Al-Qaryat region and its impact on small ruminant reproduction. 120 small ruminants were used for this study, 50 being goats and 70 being sheep from different farms. The blood samples of these animals were drawn for the purpose of carrying out a test that would determine whether they had acquired brucellosis or not. From the research, 28 had brucellosis, representing 23.3%, while 92 had not, representing 76.7% of the entire sample. In addition, it was demonstrated that animals with brucellosis had more reproductive problems compared to animals without the disease. For example, it was demonstrated that 39.3% of animals with brucellosis had abortions compared to only 9.8% of animals without the disease. In addition, it was also found that the fertility rates were low, lambing/kidding intervals were long, and stillbirths were high among the infected animals. This is supported by the statistical analysis, which showed a significant relationship between the infection of tiny ruminants by brucellosis and reproductive problems. This result unequivocally shows that brucellosis impacts the reproduction of tiny ruminants. It is therefore important to apply advanced methods of biosecurity, vaccination, and surveillance in the prevention of brucellosis in Libya.